PROJECTION MAPPING AS A MEDIUM FOR CULTURAL HERITAGE: THE CASE OF THAI MENORA (Journal of Digital System Development, 2025)
Projection mapping is a video projection technology in which video is mapped onto a surface. Then, it turns everyday objects such as buildings, walls, runways, stages, or any surface that can be manipulated in interactive displays and graphical videos. Projection mapping is very suitable for presenting creative content based on historical storytelling. It provides uniqueness to attract the public's attention to get a new experience in projection mapping and add general knowledge about history today. However, traditional methods of presenting historical narratives often struggle to capture public interest, especially among younger audiences, resulting in declining awareness and appreciation of cultural heritage. The main objective of this paper is to develop an interactive and creative storyline of the history of Thai Menora as a projection mapping for people interested in knowing about history. Next, the methodology used to make this projection mapping is the ADDIE model, which consists of analysis, design, development, implementation, and evaluation. The completed projection mapping has been successfully developed using Adobe After Effects, Adobe Audition and Filmora software, which uses content and audio elements to map the historical content. Based on the results from the usability testing on the public, all the feedback from the respondents agreed that projection mapping is very effective in presenting the storyline history of Thai Menora. Overall, the research investigated the interactive storyline history of Thai Menora through projection mapping.